The Mediating Effect of Trust on the Relationship between Attitude and Perceived Service Quality towards Compliance Behavior of Zakah - Noor, Azura Mohd; Saad, Ram Al Jaffri (International Journal of Economics and Financial Issues, 2016)
Zakah contribution to Muslim socio-economic development could not be denied by any parties. This development could be improved through incremental of zakah fund. However, the zakah collection including zakah on income is still found to be unsatisfactory due to a low level of zakah compliance. While a great deal of researches had been undertaken in the area of taxation, little is known about zakah compliance behavior and its determinants. The objective of the paper is to propose a research model in examining the influence of attitude and perceived service quality towards zakah compliance behavior, taking into consideration trust as a mediator for those relationships. Four hypotheses were drawn for this paper to be tested regarding the influence of selected variables to zakah on income compliance behavior. Moreover, theoretical and practical implications of the study, as well as suggestions for future research were also discussed. Keywords: attitude, perceived service quality, trust, zakah compliance behaviour JEL Classifications: I31, Z12, Z13, O35